2002
DOI: 10.1053/bbmt.2002.v8.abbmt080674
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for moderate-to-severe chronic graft-versus-host disease after allogeneic hematopoietic stem cell transplantation

Abstract: Among 810 consecutive hematopoietic stem cell transplantation (HSCT) patients, 679 survived more than 3 months and were evaluated for chronic GVHD. The aim of this study was to find predisposing factors increasing the risk of development of moderate-to-severe chronic GVHD. Many of the donors were HLA-identical siblings or related (n = 435), 185 were HLA-matched unrelated, and 59 were mismatched related or unrelated donors. Most of the patients had a hematological malignancy (n = 568), but 111 patients with a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 39 publications
5
57
2
1
Order By: Relevance
“…In this study, we also observed that manifestations typical of acute GVHD began after day 100 in some recipients of nonmyeloablative HCT. 7 Although previous studies have identified risk factors for acute and chronic GVHD after myeloablative HCT, [8][9][10][11][12][13][14][15] analysis of serious consequences of GVHD have not been reported after either myeloablative or nonmyeloablative HCT. The present study focused on serious consequences of either acute or chronic GVHD, using pre-specified criteria to identify fatal or disabling outcomes related to GVHD after nonmyelablative HCT.…”
mentioning
confidence: 99%
“…In this study, we also observed that manifestations typical of acute GVHD began after day 100 in some recipients of nonmyeloablative HCT. 7 Although previous studies have identified risk factors for acute and chronic GVHD after myeloablative HCT, [8][9][10][11][12][13][14][15] analysis of serious consequences of GVHD have not been reported after either myeloablative or nonmyeloablative HCT. The present study focused on serious consequences of either acute or chronic GVHD, using pre-specified criteria to identify fatal or disabling outcomes related to GVHD after nonmyelablative HCT.…”
mentioning
confidence: 99%
“…Acute GVHD was graded on a scale of 0 (absent) to IV (severe), according to previously published criteria. 12,13 The severity of chronic GVHD was defined as mild, moderate or severe, according to previously published criteria 14 and was classified by the treating physician.…”
Section: Conditioning Regimensmentioning
confidence: 99%
“…16 In addition, the contribution of primary treatment failure to the development of subsequent cGVHD was also found to be substantial, implying that patients with severe aGVHD may benefit from more aggressive treatment without delay.…”
Section: Discussionmentioning
confidence: 99%